PENGARUH KARAKTERISTIK PEKERJAAN TERHADAP KOMITMEN ORGANISASI KARYAWAN TINGKAT MANAGERIAL PERUSAHAAN JASA KONSTRUKSI DI JAWA TENGAH - INDI DJASTUTI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2011)
This study aimed to clarify the influence of job characteristics on organizational commitment of employees in construction companies. Job characteristics include skill variety, task identity, task significance, Autonomy and feedback. Meanwhile, the concept of organizational commitment is to support the interests of organizations, including affec-tive commitment, continuant commitment and normative commitment. Using multiple regression technique was found that job characteristics: skill variety, task identity, task significance, autonomy and feed-back has the effect on employee organizational commitment for construction companies.